The association between body composition measurements and blood pressure among adults in Tawang, Bachok Kelantan - Hafidah, Zolkepli (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2009)
This study investigated the association between body composition measurements and blood pressure and also to determine measures that strongly associated to blood pressure among adults in Tawang, Bachok Kelantan. This was a cross-sectional study of sixty three adults, aged between 18 to 59 years, 21 males and 42 females. This subject underwent measurement of weight and height, waist and hip circumference, body fat and visceral fat, and blood pressure. Body fat and visceral measurement was carried out through electric bioimpedance, using a Tanita body fat analyzer BC 545. Waist and hip circumference were also measured. Pearson correlation analysis was used to study the correlation of each body composition measurement with blood pressure while the stepwise multiple linear regression was used in this study to analyse the body measurement that best explained blood pressure. There is significant association between Body Mass Index (BMI) and blood pressure (P<0.01, r= 0.327). Whereas, no relationship between Waist Hip Ratio (WHR) and Blood Pressure. The percentage of body fat was also significantly correlated with blood pressure. As a conclusion, among these three measurements, the measure that strongly associated to blood pressure in this study among adults in Tawang was BMI. Otherwise, this study also revealed that the hip circumference and waist circumference were the best simple anthropometric index to assess the adult of high risk individual with cardiovascular disease together with BMI.